Statin Therapy Does Not Affect the Radiographic and Clinical Profile of Patients with TIA and Minor Stroke - Asdaghi, N.; Coulter, J.I.; Modi, J.; Camden, M.C.; Qazi, A.; Goyal, M.; Rundek, T.; Coutts, S.B. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: Acute statin therapy improves neurologic outcome and diminishes infarct growth in animal models of stroke. Clinical studies suggest that premorbid and early statin use is associated with improved outcome after major stroke. We studied the association between statin therapy and radiographic and clinical outcomes in patients with high-risk TIA and minor stroke.MATERIALS AND METHODS: Patients with high-risk TIA and minor stroke (NIHSS ≤3) were prospectively enrolled within 24 hours of symptom onset. Patients were followed clinically for 3 months, and a subset had a repeat MR imaging at 90 days.RESULTS: Of 418 patients, 23% were prescribed statins before their stroke. Statins were continued in 20% and initiated in 42%. Patients on prior statin therapy were older and more hypertensive, treated with aspirin, and more likely to have symptomatic carotid disease compared with those not on statin. Adjusting for these differences, prior statin treatment was not associated with DWI positivity (adjusted OR = 1.3; 95% CI, 0.77–2.1; P = .32) or smaller median baseline infarct volume, 1.1 mL (interquartile range = 4) versus 1 mL (interquartile range = 2.5; P = .56). Early or continued treatment with statins did not improve the risk of clinical deterioration (adjusted OR = 0.66; 95% CI, 0.27–1.6; P = .35) or poor functional outcome at 3 months (adjusted OR = 0.66; 95% CI, 0.35–1.24; P = .19).CONCLUSIONS: Prestroke or early-stroke statin therapy was not associated with a reduction in the number of DWI lesions, infarct volume, or improved clinical or functional outcome at 3 months. The effect of acute statin treatment in patients with ischemic stroke/TIA remains unclear and needs further investigation.CATCHCT and MR Imaging in the Triage of TIA and Minor Cerebrovascular Events to Identify High Risk PatientsIQRinterquartile range